Pengaruh Pemberian Insentif dan Motivasi Kerja Terhadap Peningkatan Kinerja Pegawai - Erin Yulia; M. Azis Firdaus; Syahrum Agung (Institute of Advanced Knowledge and Science, 2024)
This study discusses how incentives, work motivation affect employee performance in Cigudeg District. The purpose of this study was to test and analyze the effect of incentives and work motivation on employee performance in Cigudeg District. The sampling technique used a questionnaire technique with a total of 50 respondents who were employees of Cigudeg District. The analytical test tool used is SmartPLS v.4 with the SEM (Structural Equatoin Modeling) analysis method. The results of this study indicate that incentives have a positive and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, incentives and work motivation have a positive and significant effect on employee performance.